2000
DOI: 10.1111/j.1530-0277.2000.tb02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Working Conditions and Alcohol Use in Men and Women

Abstract: Stressful circumstances, such as adverse working conditions, were associated with high levels of alcohol intake among drinking men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…We also reported a cross-sectional study of male workers in smaller sized enterprises that showed that the frequency of heavy drinkers was higher in manual workers and transportation workers compared with white-collar workers 11) . Some studies have also reported that highly hazardous physical working conditions are associated positively with heavy and binge drinking 18,23) . A higher frequency of alcohol dependence in blue-collar workers compared with white-collar workers has also been reported 10,12) .…”
Section: Discussionmentioning
confidence: 99%
“…We also reported a cross-sectional study of male workers in smaller sized enterprises that showed that the frequency of heavy drinkers was higher in manual workers and transportation workers compared with white-collar workers 11) . Some studies have also reported that highly hazardous physical working conditions are associated positively with heavy and binge drinking 18,23) . A higher frequency of alcohol dependence in blue-collar workers compared with white-collar workers has also been reported 10,12) .…”
Section: Discussionmentioning
confidence: 99%
“…Future research should examine prospective data to determine whether work stress leads to increased body weight or whether initial body weight is a predictor of individual differences in perceived work stress and stress-induced eating (32). Second, we could not assess the effect of work stress exposure duration, because the length of the period in which the worker had been exposed to stressful work conditions was unknown to us (60). Because only long-term stress exposure is assumed to contribute to adverse physiological changes, the inability to determine exposure duration increases the likelihood of an underestimation of the associations between work stress and BMI.…”
Section: Work Stress and Body Mass Indexmentioning
confidence: 97%
“…Sociocultural studies have pointed to several environmental factors, including stress, which increase or decrease the risk for alcoholism (Hore 1971;Kushner et al 1990;San Jose et al 2000;Ragland et al 2000). Stress is any perceived challenge, either physical or psychological, real or imagined, that will disturb an individual's relatively steady internal environment, known as homeostasis, which allows optimal functioning of the organism (Selye 1946).…”
Section: Introductionmentioning
confidence: 98%